Gender Based Health Inequality and Impacting Factors - Mi Young Song; Woo Youn Lim; Jeung Im Kim (Korean Society of Women Health Nursing, 2015)
PURPOSE: This study was aimed to identify gender-based health inequality and explore impacting factors on health inequality in one province in Korea. METHODS: This was an explanatory study using the secondary data on Chungnam province from the Fifth Community Health Survey from August 16 to Oct 31, 2012. Variables included in this analysis were education level, poverty, marital status, and residential community for socio-cultural characteristics and subjective health status as an indicator of health inequality. Data were analyzed by chi2-test, t-test, ANOVA, and multiple linear regression. RESULTS: There were gender inequalities and disparities in health, and these inequalities were greater in woman than in man (chi2=161.8, p<.001). The impacting factors were education level, poverty, marital status, and residential community, which was accounted for 22.6% of variances of health inequality. Among these variables, gender showed the largest influence in health inequalities. CONCLUSION: To solve health inequalities, it should be considered gender differences based on social determinants of health. It is necessary to develop long term project based on these results and the social determinants model of World Health Organization.